THE EFFECTIVENESS OF MULTIMEDIA TOOLS IN DEVELOPING PRONUNCIATION SKILLS (Ustozlar uchun, 2025)
This article investigates the efficiency of multimedia instruments in shaping pronunciation competence in language learners. With the rapid digitalization of education, multimedia resources—such as audio recordings, interactive applications, video platforms, speech recognition software, and digital phonetic visualizers—have become indispensable components of modern language learning. The study highlights multimedia’s advantages, including enhanced phonetic awareness, increased learner motivation, real-time corrective feedback, multisensory learning engagement, and improved retention. The article concludes that multimedia tools significantly contribute to the advancement of pronunciation accuracy and fluency when applied strategically and consistently.